THE INFLUENCE OF LISTENING ANXIETY TO LISTENING COMPREHENSION OF ENGLISH EDUCATION STUDY PROGRAM STUDENTS OF SRIWIJAYA UNIVERSITY - ERLINA ERLINA; RITA INDERAWATI; RITA HAYATI (Sriwijaya University Learning and Education International Conference, 2016)
This study was intended to investigate the influence of listeninganxiety on Students’Listening Comprehension of English Education Study Program of SriwijayaUniversity and (2) the contribution of students’ listening strategies and listeninganxiety to their listening comprehension. To do so, a correlational research designwas used for the study. The participants were the second, fourth and sixth semesterstudents. A strategy questionnaire and a listening comprehension test were employedto collect the data. To analyze the data obtained, descriptive statistics and correlationanalysis were used. The findings revealed that the listening anxiety of theparticipants and their listening comprehension skill was found to be significant.listening anxiety gave significant influence to their listening comprehension